Factors Affecting Firm Value With Profitability As A Mediating Variable In Consumer Cyclicals Sector Companies - Sutrisno, Felicia; Trisnawati, Estralita; Jap, Yustina Peniyanti (Politeknik Keuangan Negara STAN, 2023)
With profitability as a mediating variable, this research aims to empirically investigate the effect of investment and financing policies on firm value. The financial reports and annual reports in 2018-2021 from the cyclicals sector listed on the Indonesia Stock Exchange (IDX) were used in obtaining research data. There were 228 research samples obtained through purposive sampling. This study uses path analysis to test the research results. The research results show that profitability is influenced by investment policies and financing policies. Firm value is not influenced by financing policy and investment policy through profitability. Firm value is significantly influenced by investment policies, profitability, and financing policies through profitability. It can be concluded that profitability is influenced by aggressive investment policies and aggressive financing policies, firm value is also influenced by aggressive investment policies.